Analysis of Students' Knowledge About Natural Disaster Mitigation in Wetland Areas - Muhsinah Annisa; Asrani Asrani; Serlinda Serlinda; Simpai Kasih; Sayyidil Maulana (Yayasan Keluarga Guru Mandiri, 2022)
Indonesia has high potential disasters. It was recorded that more than 1,800 disasters occurred in 2005-2015, of which 78% of the disasters were hydrometeorological (floods, landslides, drought, forest, and land fires). Previous research also stated that the West Kalimantan region has several threats of disasters, such as the threat of floods, landslides, forest fires, which are scattered with a percentage of the area of 82.96%. This study explores students' initial knowledge about their understanding of disaster mitigation in the Kalimantan area. This research is essential because there is no single research data that shows the condition of students' prior knowledge of disaster mitigation in Kalimantan. This research uses a quantitative descriptive approach. Samples were taken using the purposive sampling technique. Data were collected by observation and questionnaires. Data analysis techniques using percentages. Overall, the level of students' knowledge regarding natural disaster mitigation in wetlands was in the moderate category, namely 44.85%. Understanding natural disaster mitigation includes learning, emergency response planning, disaster warning, and resource mobilization. The government alone cannot take all mitigation measures in society. Therefore, disaster education is limited to school students and must also be promoted to families and communities, which is very important for elaborating mitigation knowledge.